CD36 restricts lipid-associated macrophages accumulation in white adipose tissues during atherogenesis - Chen, Vaya; Zhang, Jue; Chang, Jackie; Beg, Mirza Ahmar; Vick, Lance; Wang, Dandan; Gupta, Ankan; Wang, Yaxin; Zhang, Ziyu; Dai, Wen; Kim, Mindy; Song, Shan; et al. (Frontiers in Cardiovascular Medicine, 2024)
Visceral white adipose tissues (WAT) regulate systemic lipid metabolism and inflammation. Dysfunctional WAT drive chronic inflammation and facilitate atherosclerosis. Adipose tissue-associated macrophages (ATM) are the predominant immune cells in WAT, but their heterogeneity and phenotypes are poorly defined during atherogenesis. The scavenger receptor CD36 mediates ATM crosstalk with other adipose tissue cells, driving chronic inflammation. Here, we combined the single-cell RNA sequencing technique with cell metabolic and functional assays on major WAT ATM subpopulations using a diet-induced atherosclerosis mouse model (Apoe-null). We also examined the role of CD36 using Apoe/Cd36 double-null mice. Based on transcriptomics data and differential gene expression analysis, we identified a previously undefined group of ATM displaying low viability and high lipid metabolism and labeled them as “unhealthy macrophages”. Their phenotypes suggest a subpopulation of ATM under lipid stress. We also identified lipid-associated macrophages (LAM), which were previously described in obesity. Interestingly, LAM increased 8.4-fold in Apoe/Cd36 double-null mice on an atherogenic diet, but not in Apoe-null mice. The increase in LAM was accompanied by more ATM lipid uptake, reduced adipocyte hypertrophy, and less inflammation. In conclusion, CD36 mediates a delicate balance between lipid metabolism and inflammation in visceral adipose tissues. Under atherogenic conditions, CD36 deficiency reduces inflammation and increases lipid metabolism in WAT by promoting LAM accumulation.